2000
DOI: 10.1086/301349
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of V4334 Sagittarii (Sakurai’s Object)

Abstract: CCD UBVRi photometry of the final helium flash object V4334 Sgr (Sakurai's Object), carried out during 1997 -1999, is presented, and the light curve from its pre-discovery rise to the dust obscuration phase is constructed. The optical light curve can be divided into four sections, the rise to maximum, the maximum, the dust onset, and the massive dust shell phase. The color indices show a general increase with time, first because of the photospheric expansion and cooling, and later because of the dust forming e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 45 publications
4
53
0
Order By: Relevance
“…In order to estimate the magnitude of V4334 Sgr in such a "dustfree" lightcurve, the trend in the 1996-97 V light curve (as taken from Duerbeck et al 2000) was linearly extrapolated to August, 1998, and an "expected" magnitude of V = 10.75 was derived; if the 1997 data alone are used for an extrapolation, the result is V = 10.65. In fact, the object is observed at V = 12.55.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to estimate the magnitude of V4334 Sgr in such a "dustfree" lightcurve, the trend in the 1996-97 V light curve (as taken from Duerbeck et al 2000) was linearly extrapolated to August, 1998, and an "expected" magnitude of V = 10.75 was derived; if the 1997 data alone are used for an extrapolation, the result is V = 10.65. In fact, the object is observed at V = 12.55.…”
Section: Discussionmentioning
confidence: 99%
“…On August 12, 1998, a spectrum (range 355−1000 nm, resolving power ∼2000) was taken by A. Piemonte with Duerbeck et al (2000). The times of five spectroscopic observations, analyzed by Asplund et al (1997Asplund et al ( , 1999 and Kipper & Klochkova (1997), are indicated by open triangles.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…MV = M Bol ). The peak visual brightness for V605 Aql (Abell 58), FG Sge (Hen 1-5), and V4334 Sgr (Sakurai's object = DPV 1) has been taken from Duerbeck et al (2002), van Genderen & Gautschy (1995, and Duerbeck et al (2000), respectively. An independent distance to FG Sge based on pulsation theory has been obtained by Mayor & Acker (1980).…”
Section: Miscellaneous Distance Methodsmentioning
confidence: 99%
“…V 4334 Sgr displayed an extraordinary fast evolution from the pre-white dwarf (WD) stage to the AGB in only three years (Duerbeck et al, 2000). In addition a peculiar realtime abundance evolution has been documented for this star by Asplund et al (1999).…”
mentioning
confidence: 86%